TEMPERATURE AND PRECIPITATION REGIME IMPACT ON SPRING BARLEY (HORDEUM VULGARE) GROWTH IN PRIEKUĻI CASE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
In Latvia, the effects of drought and extreme temperatures on spring barley have so far been little studied due to the availability of data and the fact that meteorological conditions are only one of the multi-influencing factors that affect the agricultural sector.Barley usually flowers before or at the same time as ear emergence. During the flowering period high ambient temperatures are critical for yield formation. If the air temperature during flowering is above 22℃ the flowers of spring barley become sterile. From 2004 - 2022, a significant and positive correlation (R = 0,57) was observed between the average maximum daily temperature from sowing to ear emergence and the number of empty flowers in the main spike. A significant negative correlation (R = 0,55) was observed between plant height and the sum of precipitation from sowing to ear emergence and spike length and the sum of precipitation from ear emergence to maturity (R = −0,54), drought also negatively affects tillering rate and number of productive stems per plant.The combination of all the above-mentioned conditions significantly impacts the yield of barley. The following and relevant findings are very important for the agricultural sector, especially in the context of climate change.